Study on membrane roof schemes of annular crossed cable-truss structure. Issue 3 (September 2019) - Lu, Jian; Xue, Suduo; Li, Xiongyan; Liu, Renjie
Based on annular crossed cable-truss structure model with diameter of 17.15 m, the type of membrane roof was first studied. Two membrane roof schemes, cable-supported membrane roof and skeleton-supported membrane roof, were proposed. The form-finding analysis of two types of membrane roof structures was carried out. By comparative study, the strengths and weaknesses of two schemes were given, and the feasibility of skeleton-supported membrane roof was demonstrated. Second, skeleton-supported membrane roof was studied by collaborative form-finding and non-collaborative form-finding. The form-finding method being suitable for the structure was given. Finally, load analysis, parametric analysis, and dynamic characteristics of membrane and non-membrane roof structures were carried out. The results show that skeleton-supported membrane roof has the strength to resist to external loads. Poisson's ratio and self-weight have little influence on membrane roof, and arch height and pretension of membrane surface have great influence on membrane roof. The vibration modes of structure are mainly manifested as up and down vibrations accompanying with local torsion of planar cable-truss frame, which is not bad for overall structure. Meanwhile, film-covering effects of annular crossed cable-truss structure are obvious. The study contents have promoted the application of annular crossed cable-truss structure in practical engineering.